Florence : [videorecording (DVD)] : cradle of the Renaissance (View Video, 2008)
Showcases the seminal accomplishments and cultural masterpieces of innovative geniuses such as Michelangelo, Botticelli, Ghiberti, Cellini, Lorenzo de Medici, and Leonardo da Vinci.